Second hand tobacco smoke adversely affects the bone of immature rats (Clinics, 2017)
OBJECTIVES: To evaluate the influence of secondhand cigarette smoke exposure on longitudinal growth of the tibia of growing rats and some parameters of bone quality. METHODS: Forty female rats were randomly divided into four groups: control: rats were sham exposed; 30 days: rats were exposed to tobacco smoke for 30 days; 45 days: rats were exposed to tobacco smoke for 45 days; and 60 days: rats were exposed to tobacco smoke for 60 days. Blood samples were collected to evaluate the levels of cotinine and alkaline phosphatase. Both tibias were dissected and weighed; the lengths were measured, and the bones were then stored in a freezer for analysis of bone mineral content and mechanical resistance (maximal load and stiffness). RESULTS: Exposure of rats to tobacco smoke significantly compromised bone health, suggesting that the harmful effects may be time dependent. Harmful effects on bone growth were detected and were more pronounced at 60-day follow-ups with a 41.8% reduction in alkaline phosphatase levels (p